1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Quadratic equation with roots of α and β

  1. May 15, 2010 #1
    1. The problem statement, all variables and given/known data

    The quadratric equation x^2 - 5x + 7 = 0 has the roots α and β. Find the quadratic equation with roots α^3 and β^3.

    2. Relevant equations


    3. The attempt at a solution

    u = α^3
    α = u^(1/3)

    u^(2/3) - 5(1/3) + 7 = 0

    u^(1/3)[u - 5] = -7 --- minus 7 off each side followed by taking cubic root u out of the left side.

    u[u - 5] = -343 --- put everything to the power of 3.

    u^2 - 5u + 343 = 0

    but the answer is u^2 – 20u + 343 = 0

    I cannot see where I've gone wrong - help me please :) thank you
  2. jcsd
  3. May 15, 2010 #2


    User Avatar
    Science Advisor

    Well, for starters, when you cubed both sides of the equation, you forgot to cube the (u-5) term...
  4. May 15, 2010 #3


    User Avatar
    Science Advisor

    Surely you mean u= x^3 and x= u^(1/3)

    but you didn't. You should have u[u- 5]^3= -343- and multiplying that out gives a 4th degree equation not a quadratic equation.

    where you've gone wrong is in not doing what you thought you did! You did not cube the entire equation.

    You should try, instead, [itex](x- \alpha^3)(x- \beta^3)= x^2- (\alpha^3+ \beta^3)x+ \alpha^3\beta^3[/itex].

    knowing that [itex]\alpha[/itex] and [itex]\beta[/itex] satisfy [itex]x^2- 5x+ 7= 0[/itex]] tells you that [itex]\alpha+ \beta= -5[/itex] and [itex]\alpha\beta= 7[/itex].

    That makes it easy to see that [itex]\alpha^3\beta^3= (\alpha\beta)^3= 7^3[/itex].

    For [itex]\alpha^3+\beta^3[/itex] use the fact that [itex]\alpha^3+ \beta^3= (\alpha+ \beta)(\alpha^2+ \alpha\beta+ \beta^2)[/itex].

    Note that since [itex]\alpha+ \beta= -5[/itex], [itex](\alpha+ \beta)^2= \alpha^2+ 2\alpha\beta+ \beta^2= \alpha^2+ 2(7)+ \beta^2= 25[/itex] so that [itex]\alpha^2+ \beta^2= 11[/itex].
    Last edited by a moderator: May 15, 2010
  5. May 15, 2010 #4
    Thank you for the replies guys - I'll have another go :)
  6. May 15, 2010 #5


    User Avatar
    Homework Helper

    or another way of doing it:



    on cubing both sides, [tex]u(u-15u^{2/3}+75u^{1/3}-125)=-343[/tex]

    But we know from the first equation that [tex]u^{2/3}-5u^{1/3}+7=0[/tex] so then [tex]-15(u^{2/3}-5u^{1/3}+7)=-15u^{2/3}+75u^{1/3}-105=0[/tex]

    Subbing this into our result, [tex]u(u-20)=-343[/tex] hence [tex]u^2-20u+343=0[/tex] as required.
  7. May 15, 2010 #6
    Ahh - this is what I was attempting to do but failed :P

    Thank you for the input Mentallic :)
  8. May 15, 2010 #7


    User Avatar
    Homework Helper

    I had a feeling that that was the approach you were looking for :wink:
  9. May 15, 2010 #8
    I see when I was taking u^(1/3) out I only left u inside instead of u^(1/3) which messed the rest of the answer up :P
  10. May 15, 2010 #9
    Sorry - how did you get the u(u-20) part. Slightly confused by that part :S
  11. May 15, 2010 #10


    User Avatar
    Homework Helper


    Keep this in mind.

    Now after cubing we have,


    But we want to get rid of the fractional powers, and notice how the [tex]u^{2/3}[/tex] term has a multiplier of -15, let's multiply the first equation by -15.

    So looking at,




    Substitute this into the other equality,


    What do you end up with?
  12. May 15, 2010 #11
    Sorry- still not getting it :|

    from [tex]u(u-15u^{2/3}+75u^{1/3}-125)=-343[/tex] to.. [tex]u(u - 20)[/tex]
  13. May 15, 2010 #12


    User Avatar
    Homework Helper

    Ok how about this,

    let [tex]y=u^{2/3}-5u^{1/3}+7[/tex]

    therefore [tex]-15y=-15u^{2/3}+75u^{1/3}-105[/tex]

    What we have is,




    which is equivalent to,




    Notice that part in there that is equal to -15y. Let's substitute that into it then,


    Do you get this?

    But the only difference is that we had y=0, so you get the answer that you need.

    If you don't understand the process, don't use it. HallsofIvy's method is perfectly fine too.
  14. May 15, 2010 #13
    I fully understand now - thank you very much :D
  15. May 19, 2010 #14
    [itex]\alpha^3+ \beta^3= (\alpha+ \beta)(\alpha^2 - \alpha\beta+ \beta^2)[/itex].
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook